Edukasi Dampak Brain Rot terhadap Konsentrasi dan Motivasi Belajar Peserta Didik di Era Digital pada SMP Negeri 103 Maluku Tengah - Dewilna Helmi (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2026)
Rapid developments in digital technology have had a significant impact on students’ lives, particularly in the use of social media and excessive consumption of digital content. The phenomenon known as Brain rot has become a growing concern because it can affect students’ concentration, learning motivation, and quality of thinking. This study aims to provide education regarding the impact of brain rot on students’ concentration and learning motivation in the digital era. The activities were carried out through counseling methods, interactive discussions, and mentoring for junior high school students. The materials presented included the definition of brain rot, the effects of excessive digital media use, the importance of learning time management, and strategies to improve learning focus. The results of the activity showed that students gained a better understanding of the negative impacts of uncontrolled digital media use. In addition, students began to realize the importance of limiting gadget use and increasing productive learning activities. This educational program also helped raise students’ awareness of the importance of maintaining mental health and cognitive abilities amid the rapid development of digital technology. Through this educational activity, students are expected to use technology wisely so that their concentration and learning motivation can improve optimally. Educational programs regarding brain rot need to be carried out continuously as part of strengthening digital literacy within the school environment.